FRI0148 Remission rates increase substantially by adding adalimumab to methotrexate and intra-articular glucocorticoid in patients with early rheumatoid arthritis - 1-year results of investigator-initiated, double-blinded randomized clinical trial (OPERA). (23rd January 2014) - Hørslev-Petersen, K.; Hetland, M.L.; Junker, P.; Pødenphant, J.; Ellingsen, T.; Ahlquist, P.; Lindegaard, H.; Linauskas, A.; Schlemmer, A.; Dam, M.Y.; Hansen, I.; Horn, H.C.; et al.
Abstract : Background: In the CIMESTRA Study patients with early rheumatoid arthritis (RA) were treated with methotrexate (MTX) and intra-articular glucocorticoid. This led to results comparable to biological trials with 34%/28% of pts in DAS28/ACR remission after 1 year (1, 2). Objectives: We studied if addition of adalimumab (ADA) to the CIMESTRA strategy is of further therapeutic benefit. Methods: DMARD naïve early RA patients with disease duration <6 months (n=180) were randomized 1:1 to MTX 7.5 mg weekly + ADA 40 mg eow or MTX + placeboADA (PLA). MTX was increased to 20 mg/week within two months. Treatment target was low disease activity (DAS28(CRP) <3.2). Injections of triamcinolone were given into swollen joints (max. 4 joints/4 ml/visit). Oral prednisolone was not allowed. Sulfasalazine 2 g/day and hydroxychloroquine 200 mg/day were added if DAS28(CRP) >3.2 after three months. Efficacy was assessed by DAS28(CRP), CDAI, SDAI and ACR/EULAR Boolean remission criteria. Primary analysis was by ITT with last observation carried forward. Completer analysis and ITT without imputations gave similar results (not shown). Values are medians (5%/95% percentiles) or percentage. We used Mann-Whitney or Pearson's chi-square tests. Results: Baseline characteristics were similar between MTX+PLA/MTX+ADA groups: Women: 69%/63%; age: 54.4/56.2 years; disease duration: 83/84 days; anti-CCP positive: 70%/60%; IgM-RF positive: 74%/70%; DAS28(CRP): 5.6/5.5; HAQ: 1.0/1.1 (all NS). Triple therapy was added in 25/17 patients (p=0.25). Treatment target was reached in 46%/58% (MTX+PLA/MTX+ADA) at 1 month, 63%/73% (2 months), 70%/76% (3 months), and 76%/80% (12 months) (NS between groups at all time points). However, in the MTX+ADA group significantly more patients achieved rapid and sustained clinical remission as assessed by DAS28, CDAI, SDAI and ACR/EULAR remission criteria (table ). Number needed to treat (NNT) with ADA to achieve remission in one extra patient at 1 year was 4 to 5.9 depending on remission criteria. Conclusions: Low disease activity was achieved by ≈ 80% in both groups, but remission rates increased considerably by adding adalimumab to methotrexate and intraarticular glucocorticoid injections in DMARD naïve patients with early RA. References: Hetland et al: Arthritis Rheum 2006;54:1401-09. Hetland et al: Ann Rheum Dis 2008;67:815-22. Disclosure of Interest: K. Hørslev-Petersen Grant/Research support from: Abbott, M. Hetland Grant/Research support from: Abbott, Bristol-Meyers Squibb, Roche, Schering-Plough/MSD, UCB-Nordic, and Wyeth/Pfizer, Speakers Bureau: Abbott, Centocor, Roche, Schering-Plough/MSD, UCB-Nordic, and Wyeth/Pfizer, P. Junker: None Declared, J. Pødenphant: None Declared, T. Ellingsen: None Declared, P. Ahlquist: None Declared, H. Lindegaard Speakers Bureau: Roche, A. Linauskas: None Declared, A. Schlemmer Speakers Bureau: MSD, Roche, M. Dam: None Declared, I. Hansen: None Declared, H. Horn: None Declared, A. Jørgensen: None Declared, S. Krintel: None Declared, J. Raun: None Declared, C. Ammitzbøll: None Declared, J. Johansen: None Declared, M. Østergaard Grant/Research support from: Abbott, Amgen, Bristol-Myers Squibb, Centocor, Genmab, Glaxo-Smith-Kline, Mundipharma, Novo, Pfizer, Roche, Schering-Plough, UCB and Wyeth., Speakers Bureau: Abbott, Amgen, Bristol-Myers Squibb, Centocor, Genmab, Glaxo-Smith-Kline, Mundipharma, Novo, Pfizer, Roche, Schering-Plough, UCB and Wyeth., K. Stengaard-Pedersen Grant/Research support from: Abbott